Knowledge and Information Exposure About Family Planning Among Women of Reproductive Age in Informal Settlements of Kira Municipality, Wakiso District, Uganda - Birabwa, Catherine; Chemonges, Dennis; Tetui, Moses; Baroudi, Mazen; Namatovu, Fredinah; Akuze, Joseph; Makumbi, Fredrick; Ssekamatte, Tonny; Atuyambe, Lynn; Hernandez, Alison; Sewe, Maquins Odhiambo (Frontiers in Global Women's Health, 2021)
Introduction: A high unmet need for family planning (FP) prevails in sub-Saharan Africa. Knowledge, awareness creation, and ensuring accessibility are frequently used to increase FP uptake. However, evidence on knowledge or information dissemination about FP among marginalized populations in urban settings in Africa is limited. This study explored the knowledge of FP methods, media exposure, and contact with FP providers among women from an informal settlement in Uganda. Methods: Using a cross-sectional study design, we interviewed 626 women aged 15–49 years living in informal settlements of Kira municipality, selected through multistage sampling. Using a standard questionnaire, data was collected on socioeconomic characteristics, knowledge of FP methods, and access to media FP messages among others. Binomial log-linear regression was used to assess disparities in exposure to media FP messages or provider information. Data were analyzed using STATA version 14, at a 5% level of statistical significance. Results: Nearly all women in the survey were aware of FP methods (99.7%). On average, each woman was aware of 10 FP methods. The most commonly known methods were male condoms (98.2%), injectables (97.4%), and the oral contraceptive pill (95.2%). Use of any contraceptive was found among 42.7% of respondents. Exposure to media was found in 70.6% of the respondents, mostly through television (58.5%) and radio (58.3%). Discussing FP with a provider was significantly associated with media exposure (aPR 1.4, 95% CI: 1.24–1.56). Less than 50% of women who were not using FP had contact with an FP provider. Women in union (aPR 1.6, 95% CI: 1.01–2.68) and those with access to media messages (aPR 2.5, 95% CI: 1.37–4.54) were more likely to have contact with a provider to discuss FP. Conclusion: There is high general awareness about FP methods and media exposure, but method use was low. Further exploration of women's understanding of FP methods and the fit between existing education programs and FP knowledge needs in this urban setting should be conducted. The potential for mobile health solutions in this urban population should be explored. Future studies should focus on the knowledge and understanding of FP among unmarried and nulliparous women and those with no access to media information.